ARTIFICIAL INTELLIGENCE AND MORAL RIGHTS - Ruxandra VIȘOIU (Challenges of the Knowledge Society)
Artificial Intelligence or AI, for short, has been a subject of great interest in the last few years. Its understanding and implementation raise many questions about how our world will look like in the future. These matters have greatly impacted the legislative field, along with the fields of technology, security education - and the list stays open. This paper aims to highlight the main key aspects of AI, its current legal framework (or, rather, lack thereof), along with a more in-depth analysis of moral rights in the field of AI.